Association of Insulin Resistance, Lipid Profile, Hormonal Imbalance, and Gastrointestinal Metabolic Parameters in Women with Polycystic Ovary Syndrome Receiving Metformin Therapy - Razwan Ashraf, Rehana Bibi, Farah Saleem, Yusra Khalid, Nazneen Akhtar, Sheema Khan, (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Polycystic ovary syndrome (PCOS) is a complex endocrine–metabolic disorder characterized by insulin resistance, dyslipidemia, androgen excess, and hepatic metabolic disturbances. Metformin is widely prescribed to improve insulin sensitivity; however, its broader metabolic and gastrointestinal effects remain incompletely defined in routine clinical settings. Objective: To evaluate the association of insulin resistance, lipid profile, hormonal imbalance, and gastrointestinal metabolic parameters in women with PCOS receiving metformin therapy over a six-month period. Methods: This prospective observational study included 90 women diagnosed with PCOS at Aziz Bhatti Shaheed Teaching Hospital, Gujrat, and the Department of Gynaecology & Obstetrics, KRL Hospital, Islamabad, from February 2022 to January 2023. Baseline clinical, metabolic, hormonal, and hepatic parameters were assessed and compared with six-month post-treatment values. Key outcomes included changes in HOMA-IR, lipid profile, reproductive hormones, and hepatic metabolic markers including ALT, AST, GGT, and the Hepatic Steatosis Index (HSI). Statistical analysis was performed using paired comparisons, correlation testing, and multivariable regression modeling. Results: Eighty-four participants completed the study. Metformin therapy significantly reduced fasting insulin and HOMA-IR (3.98 ± 1.55 to 2.78 ± 1.29; p < 0.001) and improved lipid parameters including triglycerides and LDL-C. Hormonal improvements included reduced total testosterone and increased SHBG, with a corresponding decrease in LH/FSH ratio. Gastrointestinal–metabolic indices demonstrated favorable changes, including reductions in ALT, GGT, and HSI. Higher baseline BMI and HOMA-IR were independent predictors of greater improvement in insulin resistance. Conclusion: Metformin therapy leads to meaningful improvements in insulin resistance, lipid abnormalities, androgen excess, and hepatic metabolic stress in women with PCOS. These findings underscore the importance of comprehensive metabolic monitoring and support metformin as a cornerstone therapy in the integrated management of PCOS. Keywords: Polycystic ovary syndrome; Metformin; Insulin resistance; HOMA-IR; Dyslipidemia; Hyperandrogenism; Liver enzymes; Hepatic Steatosis Index.